PENANGANAN KENAKALAN REMAJA TERKAIT TAWURAN OLEH POLSEK PASAR MINGGU - Aleksiva Nouvalsukma, Fairuz; Subowo, Ari; Santoso, R. Slamet (Journal of Public Policy and Management Review, 2024)
Brawls are a frequent form of juvenile delinquency in the Pasar Minggu area, necessitating the intervention of the Pasar Minggu Police Sector. According to Indonesian law (Undang-undang Nomor 2 Tahun 2002), the police are tasked with maintaining public order and security, enforcing laws, and providing community services. However, field observations reveal that the performance of Polsek Pasar Minggu in handling juvenile delinquency, specifically brawls, remains suboptimal. This study utilizes Agus Dwiyanto's (2006) organizational performance theories and Ruky's factors of organizational performance, employing qualitative descriptive methods including observation, documentation, and interviews. Findings indicate inefficiencies in efficiency, effectiveness, fairness, and responsiveness, influenced by technology, input quality, physical environment, organizational culture, leadership, and human resource management. Recommendations are provided to improve these dimensions.